Law, politics, and society - d; Cichowski, Rachel A.; Oxford eBooks (Oxford : Oxford University Press, 2003)
The contributors to this volume take the dynamic interaction between law, politics and society as a starting point to think critically about recent developments and future innovations in European integration and EU studies.
Description based on print version record.
Includes bibliographical references and index.
Keywords: European Union; Law -- Political aspects -- Europe Union countries; Sociological jurisprudence -- European Union countries; European Union countries -- Politics and government; Electronic books